2018
DOI: 10.1002/aoc.4250
|View full text |Cite
|
Sign up to set email alerts
|

Biological contour, molecular docking and antiproliferative studies of DNA targeted histidine based transition metal(II) complexes: Invention and its depiction

Abstract: A novel series of histidine derived transition metal complexes were synthesized and characterized by multispectral techniques such as UV-Vis., FT IR, EPR, NMR, ESI-mass analysis and other physico-chemical methods like elemental analysis, molar conductivity, magnetic susceptibility. The synthesized compounds were attempted for their biological prospective. The biological studies involved are DNA interaction (binding and damage), antimicrobial, antioxidant, antiproliferative and molecular docking. DNA interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…UV absorption at 260 and 280 nm had a ratio (A 260 /A 280 ) of 1.83 (usually around 1.8-1.9), which indicated that the prepared CT-DNA solution was sufficiently free of protein contamination. [1,[37][38][39][40] The stock solution was stored at 4°C and was utilized within 4 days. The concentration of ethidium bromide was specified at 480 nm (ε = 5860 M −1 cm −1 ).…”
Section: Biological Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…UV absorption at 260 and 280 nm had a ratio (A 260 /A 280 ) of 1.83 (usually around 1.8-1.9), which indicated that the prepared CT-DNA solution was sufficiently free of protein contamination. [1,[37][38][39][40] The stock solution was stored at 4°C and was utilized within 4 days. The concentration of ethidium bromide was specified at 480 nm (ε = 5860 M −1 cm −1 ).…”
Section: Biological Investigationmentioning
confidence: 99%
“…The quest to discover modern antimicrobial and anticancer drugs with broad-spectrum activity has been reinvigorated by the proliferation of antimicrobial renitent microbial descents. [1][2][3] Interest in the chemistry of metal chelates of tridentate ONO imines has increased in the last few decades [4][5][6][7] due to the wide implementations of those metal chelates in numerous domains. Transition metal chelates have been found to catalyse water photolysis under specified experimental conditions.…”
mentioning
confidence: 99%
“…The DNA binding studies of electronic absorption, viscosity measurements, DNA cleavage, cytotoxicity activity are followed according to the previously reported procedures. [18] The materials and methods, Fluorescence binding studies, antimicrobial activity, antioxidant activity, and molecular docking details are given in supporting information (S1).…”
Section: Methodsmentioning
confidence: 99%
“…Amino acid derived transition metal complexes were synthesized by using our previously reported Schiff base ligand (E)-4-((4-chloro-3-nitrobenzylidine)amino)-1,5dimethyl-2-phenyl-1H-pyrazol-3(2H)-one. [18] A 5 mmol of the ligand and 5 mmol of metal (II) chlorides were mixed with 50 ml of methanol and stirred with refluxed for ca. 2 hr and then, a 10 mmol of L-tryptophan in water: methanol (1:1) mixture was added to the above mixture while continuous stirring with reflux for ca.…”
Section: Synthesis Of Metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation